ANALYSIS OF NON-TARIFF BARRIER POLICIES FOR INDONESIAN TIRE INDUSTRY: A SYSTEM DYNAMICS APPROACH - ARMAN SINAGA - NIM: 23415055 , RUDY
This study presents a framework to analyze the effect of non-tariff barrier (NTB) policy in Indonesian tire industry. NTB restricts imports or exports of goods or services through mechanisms other than the simple imposition of tariffs. Based on system dynamics, we develop a qualitative framework describing the dynamic behavior of the Indonesian tire industry, and the proposed framework is used to analyze the potential impact of several NTBs. The analysis results show that the NTB policies should be implemented with care. NTB based on mandatory standard is only effective in short term, and subsidy based NTB limits the local companiesÃ‚Â’ incentives to enhance the productivity. Restriction in import license is ineffective unless local companies invest in capacity. The proposed framework can serve as a decision aid to enhance the quality of the policy making.